As Filhas do Arco-Íris, de Eulício Farias de Lacerda : mitos, lendas e contos populares como elementos estruturantes do romance - Silva, Eldio Pinto da (2008)
The corpus of this work constitutes an analysis the literary work As Filhas do Arco-Íris, by Eulício Farias de Lacerda, considering object of study myths, legends and popular stories as estruturant elements of the romance. The unchainment of this reading considers aspects of the oral tradition as starting point for the rupture tradition. In that perspective, it became fundamental to describe aspects of the popular culture that consolidated the Brazilian Literature during the 20th century. Like this, it was necessary to understand the development of oral elements and the structuring of the folk-tales, pointing out that As Filhas do Arco-Íris was built in a especial way with regionalist characteristics, following the parameters of the romances published among the years 1930 and 1950. In the researched work, it was noticed a narrative that gathers stories, legends, myths, proverbs and oral locutions. In this, it reveals that the Brazilian literary production grew in aesthetics and thematic. Like this, As Filhas do Arco-Íris is an exercise of the experience regionalist inserted in the contemporary novel, because even with your first publication in 1980, the narrative is configured to the molds of a Romance de 30